Austronesian Languages in Papua. A Description of its Phonological and Grammatical Aspects (Global Journal of Human-Social Science, 2013)
The unique place in the globe which owns almost thousands of languages is found in New Guinea Island one of the languages belongs to Austronesian languages are the primary focus in this article These languages and other languages in this island are noted to be gigantic assets to linguists who are interested in exploring the distinctive languages in the world in the area of linguistics The article aims at presenting the historical description of Austronesian languages including its characteristics Its phonological and grammatical aspects are presented to demonstrate the uniqueness of these languages used by speakers who have typical characteristics of the Austronesian cultural back-grounds A brief history of Austronesian culture is also provided The word Papua used to be called Irian Jaya in the above title is the name of the Eastern Province belongs to the Republic of Indonesia This province shares border with Papua New Guinea PNG
Keywords: nan (non austronesian); an (austronesian); an1 (austronesian 1); an2 z (austronesian 2)